Fuegian Museums and Anthropological Discourses: A Comparison of the Representations of Indigenous Societies from Tierra del Fuego in the Two Southernmost Museums in the World (Museo del Fin del Mundo, Argentina, and Museo Antropológico Martín Gusinde, Chile). (10th September 2019) - Fiore, Danae; Butto, Ana
Abstract: In this essay, we analyze the museum scripts and exhibitions at the two southernmost museums in the world: Museo del Fin del Mundo (MFM, Ushuaia, Argentina) and Museo Antropológico Martín Gusinde (MAMG, Puerto Williams, Chile). The research focuses on the representations of Fuegian Indigenous peoples who inhabited (and still inhabit) Tierra del Fuego. To this end, comparative analyses are based on ( a ) the Indigenous societies represented; ( b ) the types of materials exhibited (archaeological, ethnographic, contemporary); ( c ) the uses of oral/written/photographic information; and ( d ) the types of museum displays used in each display case. The analyses aim to identify and discuss the different underlying anthropological discourses about the Indigenous Fuegian societies, their associations with past and present, prehistoric and historical events in Chile and Argentina, their visibility as "subjects" and/or "agents" within the contemporary local Fuegian communities, and their involvement in the formation of the museum's exhibitions.